WAHOSAN BUJANG GENJONG: NASKAH KUNO TASAWUF DARI BUMI CIREBON - Muhamad Mukhtar Zaedin (IAIN Syekh Nurjati Cirebon, 2017)
AbstractThe paper discusses one ancient manuscript stored by the Rumah Budaya Pasambangan Jati; Wahosan Bujang Genjong. Manuscript in the form of the tembang macapat tells about the figure of Bujang Genjong and Rara Gonjeng who in love. The requirement of